Linac-based fractionated stereotactic radiotherapy with a micro-multileaf collimator for large brain metastasis unsuitable for surgical resection. (17th June 2020) - Matsuda, Ryosuke; Tamamoto, Tetsuro; Sugimoto, Tadashi; Hontsu, Shigeto; Yamaki, Kaori; Miura, Sachiko; Takeshima, Yasuhiro; Tamura, Kentaro; Yamada, Shuichi; Nishimura, Fumihiko; Nakagawa, Ichiro; Motoyama, Yasushi; et al.
Abstract: The aim of this study was to assess clinical outcomes using linac-based, fractionated, stereotactic radiotherapy (fSRT) with a micro-multileaf collimator for large brain metastasis (LBM) unsuitable for surgical resection. Between January 2009 and October 2018 we treated 21 patients with LBM using linac-based fSRT. LBM was defined as a tumor with ≥30 mm maximal diameter in gadolinium-enhanced magnetic resonance images. LBMs originated from the lung ( n = 17, 81%), ovary ( n = 2, 9.5%), rectum ( n = 1, 4.8%) and esophagus ( n = 1, 4.8%). The median pretreatment Karnofsky performance status was 50 (range: 50–80). Recursive partition analysis (RPA) was as follows: Classes 2 and 3 were 7 and 14 patients, respectively. The median follow-up was 5 months (range: 1–86 months). The range of tumor volume was 8.7–26.5 cm 3 (median: 17.1 cm 3 ). All patients were basically treated with 35Gy in 5 fractions, except in three cases. The progression-free survival was 3.0 months. The median survival time was 7.0 months. There was no permanent radiation injury in any of the patients. Radiation-caused central nervous system necrosis, according to the Common Terminology Criteria for Adverse Events version 4.0, occurred in one patient (grade 3). One patients received bevacizumab for radiation necrosis. Two patients underwent additional surgical resection due to local progression and cyst formation. For patients with LBM unsuitable for surgical resection, linac-based fSRT is a promising therapeutic alternative.